The handbook of humanitarian law in armed conflicts - Dieter Fleck; in collaboration with Michael Bothe (Oxford University Press, 1995)
This book offers the most up-to-date authoritative commentary and analysis of international humanitarian law applicable in armed conflict. While the past few decades have seen consistent development of the laws culminating in a series of International Covenants and Protocols, world events in recent years have made reassessment of the law both a timely and topical concern. In this new book, acknowledged experts restate the international humanitarian law applicable in armed conflict. The key statements were promulgated as the Joint Service Regulation for the German Armed forces in August 1992 and this book will serve as a work of reference for practicing lawyers and academics and as a work of legal instruction to armed forces